The Development of Aqidah Education Models Based on The Qur'an and Hadith for Early Childhood in Parenting Activities - Masganti Sit; Farida Jaya; Khairunnisa Khairunnisa (Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to develop a model of faith education in the Qur'an and hadith for early children in parenting activities. Research development or Research and Development (R&D) is used as a methodological type of educational product development, namely the type of research used to produce a product or test the effectiveness of a product. The focus of this research is on the implementation, the steps for developing the educational model, the implementation of parenting, the participants' responses to the educational model, and the results of the evaluation of parenting activities for early childhood (4-5 years) at RA Rabbani Islamic School. The results of this study are in the form of guidebooks (modules) about the model of aqidah education in the Qur'an and hadith for early children which can be used as learning resources that have a real effect in parenting activities.